Analisis Pengelolaan Wisata Sawah Halal Dalam Meningkatkan Kesejahteraan Masyarakat di Desa Sidua-Dua Kabupaten Labuhanbatu Utara - Juwita Wulandari Dalimunthe; Muhammad A rif; Nurul Jannah (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
Increasingly high needs make tourism a basic part of human lifestyle, and move people to get to know nature and culture in other countries. So indirectly the movement of people will affect the mutually sustainable economic chain. In this paper regarding the management of halal rice field tourism in improving the welfare of the community in Sidua-dua Village, North Labuhanbatu Regency. Therefore the aim of this study is to identify and determine the physical carrying capacity of the potential of rice fields in supporting tourism activities and find out whether rice fields have been managed optimally so that the potential of the rice fields is able to prosper the surrounding community. This research uses a type of field research (Field Research). With the nature of this research it is descriptive qualitative. The results of this study show that the Halal Labura Rice Field Tourism has very good economic potential where economically the Labura Halal Rice Field Tourism increases value from agriculture to the economic sector. This is supported by a strategic location, affordable travel tickets and attractive tourist facilities. However, Sawah Labura Halal Tourism has weaknesses, namely during the harvest season and weather changes even though it has been tricked by changing photo spots every time every three months. Keywords Management, Potential of Rice Fields, Community Welfare